Analysis of Directive Speech Acts by Indonesian Language Teachers at SMP Negeri 03 Tawangsari - Hanifah Nur Aini; M Markhamah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The purpose of this study is to determine the forms of directive speech acts used by Indonesian language teachers at SMP Negeri 03 Tawangsari. A qualitative descriptive method was used in this study. The data source for this study was the directive speech acts given to students by Indonesian language teachers at SMP Negeri 03 Tawangsari. This study examined verbal data from teachers and students at SMP Negeri 03 Tawangsari during the Indonesian language learning process in the form of directive speech acts. In communication, this data serves as a means of conveying messages. The data collection techniques used in this study included free listening, recording, note-taking, and interviewing techniques. Data analysis in this study used data analysis techniques by listening, understanding, organizing, categorizing, connecting categories, and interpreting data based on context. In this study, the researcher used the triangulation method to test the validity of the data. The research findings from the direct teaching of Indonesian language teachers included 32 data: 10 data in the form of direct teaching in commands, 9 data in the form of direct teaching in requests, 5 data in the form of direct teaching in advice, 5 data in the form of direct teaching in prohibitions, and 3 data in the form of direct teaching in invitations. In other words, there are five types of direct teaching in Indonesian at SMP Negeri 03 Tawangsari: commands, requests, advice, prohibitions, and invitations.